The physical background (Scottish Historical and Archaeological Internet Reports, 2003)
This chapter considers geology, machair geomorphology in the Western Isles, the agricultural capability of the machair units (the low machair plain, the high machair plain and the dune systems), climate, the physical landscape as a settlement resource, landscape formation, the chronology of machair formation and of peat formation.